Penerapan Model Pembelajaran Kooperatif Tipe Think, Talk, Write (TTW) dalam Meningkatkan Keterampilan Menulis Berita pada Siswa Kelas VII F SMPN 4 Watampone - Nita Juliana; Andi Tenri Sua; Suhardiman Suhardiman (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to improve the writing skills of news texts for grade VII students of SMPN 4 Watampone through the application of the Think, Talk, Write (TTW) learning model. The background of this study is the low skill of writing students' news texts as shown by the average score that is below the Minimum Completeness Criteria (KKM), which is 70. The research method used is Class Action Research (PTK) which is carried out in two cycles. The research subjects consisted of 32 students in grade VII F SMPN 4 Watampone for the 2024/2025 school year. The research instruments include test instruments in the form of news text assessment aspects, and non-test instruments in the form of observation sheets. The data collection techniques used are test and non-test techniques to identify improvements in student learning outcomes. The data analysis techniques used are quantitative and qualitative analysis. The results of the study showed an increase in the ability and skills to write news texts from cycle I to cycle II. In the first cycle, the number of students who achieved the KKM score was 9 people (28%), while in the second cycle it increased to 28 students (78%). Thus, the application of the Think, Talk, Write (TTW) learning model has proven to be effective in improving students' news text writing skills.